Dr.RPS essential procedures for safe maternity care : a guide book for Philippine nurses and midwives - Salustiano, Rosalinda P. (Quezon City, Philippines : C & E Publishing Inc., 2010)
This third editionis written for the main purpose of continuing the commitment of sharing with students and practitioners of nursing and midwifery the author's great enthusiasm and passion for relevance in the practice of maternity and newborn nursing.
Unit 1: The nurse-maternity client relationship -- Unit 2: Pregnancy -- Unit 3: Childbirth -- Unit 4: Postpartum care -- Unit 5: Newborn care
Includes bibliographical references and index.
Keywords: MATERNAL HEALTH SERVICES